THE COMPARISON BETWEEN PLYOMETRICS EXERCISE WITH AEROBIC EXERCISE TOWARDS DECISION-MAKING IN YOUNG ADULTS - Azzahara, Salma Yasmine; Ambarwati, Endang; Kumaidah, Endang; Widodo, Sumardi (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Lack of physical activity in individual has a big impact towards brain as if in the cognitive parts of the brain, especially decision making and memory. The relation between physical activity and cognitive ability is related to angiogenesis and neurogenesis that is more optimal in individuals who do their physical activity routine. Plyometrics and Aerobic exercise are proven to have a positive effect on the body, but there has been no further research on the comparison of the two sports.  Aim: to understand the comparison between plyometrics exercise with aerobic exercise towards decision-making in young adults . Methods: This study used quasi experimental design pretest and posttest. The subjects were 39 aged, all of whom are students of Fakultas Kedokteran Universitas Diponegoro. Subjects divided into 3 groups as control, Plyometrics exercise, and Aerobic exercise. Decision-making score measured by IOWA Gambling Task (IGT). Data’s significance was analyzed with paired t-test.  Results: There was significant difference in decision-making score before (pre-test) and after (post-test) Plyometrics and Aerobic exercise (p<0,05). Nevertheless, higher score was found in experimental group 1 which is the Plyometrics exercise (p=0,000). Furthermore, there was significant difference towards decision-making score in experimental and control group (p<0,05). Conclusion: Plyometrics and Aerobic exercise increase decision-making score for young adults. A more significant increase was found in the Plyometrics group (p=0,000).